Determining the value of cooling in photovoltaics for enhanced energy yield. (1st January 2018) - Duck, Benjamin C.; Fell, Christopher J.; Anderson, Kenrick F.; Sacchetta, Claude; Du, Yanping; Zhu, Yonggang
Highlights: We derive equations for the cost-effectiveness of cooling a PV device in the field. Variables are cooling power, climate, installation type, temperature coefficient and module efficiency. Breakeven cost ranges from ∼$1/m 2 to ∼$44/m 2 depending on circumstances. Abstract: Methods for cooling photovoltaic (PV) modules to increase their output have been proposed several times in the literature. Most of these reports describe the increase in power output achieved, but they rarely comment on the economic cost-benefit proposition. Where the economics have been considered, this has been based on measurements for the authors' specific PV system at a specific site. This means the economics are not easily interpreted for other systems at other sites. We derive a theoretical formulation for quantifying the economic value of artificial cooling of PV modules. The formulation is not specific to any particular method of cooling. It takes as input the rate of heat removal that a cooling method can provide (in Wm –2 or Wm –2 K −1 ) and determines the economic value of this cooling rate, based on variables including local solar conditions, capital cost of the system, system ventilation, plus the temperature coefficient and efficiency of the modules. We find that the economic value of cooling PV depends strongly on the system design and local conditions, with favourable circumstances leading to a viable cost of potentially over $40/m 2, however unfavourable circumstances are many times less attractive at less than $1/m 2 . The equations presented can be used to optimise the design of a cooling feature that is applied to a PV module or system, provided the above parameters of the cooling feature and PV system are established.